Effect Corporate Governance on CSR with COVID-19 as moderation: Mining Companies Listed on IDX - Hesniati Hesniati; Eddy Oktarianto (Islamic University of Kalimantan MAB Banjarmasin, 2024)
Influence of corporate governance on corporate social responsibility activities with the moderating variable COVID-19 is still rarely studied in Indonesia and has attracted attention for research. The purpose of this study was to determine the effect of corporate governance on corporate social responsibility with the COVID-19 moderating variable. The sample for this research is mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2021 with a final sample of 36 companies out of 56 companies. This study uses simple linear regression to determine and predict the value of one variable against another. The result of this study is that the independent variables board size and institutional ownership have a significant positive relationship and foreign ownership variables have a negative significant relationship. In addition, variables managerial ownership, gender diversity and board independence do not have a significant relationship. For the moderating variable COVID-19 only partially affects to independent variables and the dependent variable.